Estimation of surface energy fluxes from bare ground in a tropical station using priestleytaylor method (2013)
This investigation was designed to test the performance of Priestley Taylor method in the partitioning of the available energy into sensible and latent heat fluxes in a tropical site. Compared to eddy covariance measured fluxes, the conventional Priestley Taylor constant (aPT) of 1.25 gave low coefficient of determination and high bias error for both sensible and latent heat fluxes. It overestimated latent heat flux in the noon and afternoon but underestimated sensible heat flux. The bias error reduced and the coefficient of determination increased for sensible heat flux when aPT value was reduced to 1.0. The bias error for latent heat also reduced but the coefficient of determination did not change with the reduction in aPT value. The root mean square error reduced with the reduction in the aPT value. Compared to measured fluxes, coefficient of determination of sensible heat flux ranged from 0.82 to 0.90 while that of latent heat flux ranged from 0.78 to 0.9. Priestley Taylor method is recommended for partitioning of available energy into its component sensible and latent heat fluxes.